Capaian Kepuasan Kerja dengan Teamwork pada Divisi Produksi PT. GIS - Riris Laili Faidah; Agus Frianto (Jurnal Ilmu Manajemen, 2023)
Job satisfaction is an essential factor in human resource management. Several factors that can affect job satisfaction are organizational culture and teamwork. This study aims to analyze the effect of organizational culture on employee job satisfaction through teamwork for employees in the production division at PT X. This study uses quantitative analysis with a total population of 139 employees consisting of 3 teams, there are gross production, evisceration, and net production. The total sample in this study was 40 respondents from the production division. The statistical analysis of this research is PLS (Partial Least Square) with SmartPLS 4.0 software. The results of this study indicate that organizational culture has no significant effect on job satisfaction, organizational culture has a positive effect on teamwork, teamwork has a positive effect on job satisfaction, and teamwork has successfully mediated the influence of organizational culture on job satisfaction of production employees at PT X.